The Power of Boldness: Ten Master Builders of American Industry Tell Their Success Stories - Blout, Elkan (The National Academies Press, 1996)
"Whatever you dream, begin it, for boldness has genius, power and magic in it." -Goethe What qualities brought America to its dominance of world industry? How will American technology fare in the new global marketplace? What upbringing, education, and personal traits are required to produce leaders who can succeed in this new world? Scan the bookstore shelves and you'll see dozens of attempts by authors to capture the essence of leadership and entrepreneurial success. In The Power of Boldness, the answers come from original sources: ten of the country's most successful business leaders, who share their experiences and insights in individual essays that are remarkable for their directness and personal detail. Six of the writers are inventors who created the enterprises to commercialize their ideas—four assumed management of their fathers' companies and moved into new industrial and geographic markets. Born between 1897 and 1962, these outstanding figures collectively chronicle America's industrial rise since World War II—and share their perspectives on what lies ahead in the age of technology. In engaging and often humorous terms, these men describe how they managed to make the most of the economic and social ups and downs of the past decades—how boldness, clear thinking, and a willingness to learn saw them through the bad times and paved the way to their success. No other book gathers so distinguished a group of business figures:

Memorial Tributes: Volume 21 - National Academy of Engineering (The National Academies Press, 2017)
This is the 21st Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964.

Robo World: The Story of Robot Designer Cynthia Breazeal - Brown, Jordan D. (The National Academies Press, 2006)
Cynthia Breazeal is a creature creator. Armed with electronic gadgets, software programs, and her endless imagination, she creates lifelike machines that can respond to the world around them. Cynthia Breazeal is a roboticist, a scientist who designs, builds, and experiments with robots. As a child, she relied on movies to see robots in action. Now robots are part of her daily life at the MIT Media Lab. There, she and her students use their computer science and engineering skills to work on marvels like Leonardo, a robot that interacts with people in ways that seem almost human. Cynthia's other world-famous projects include Kismet, an emotionally intelligent robot that smiles, frowns, and babbles like a baby. Why create robots like these? Cynthia can picture a future where sociable robots exist to benefit people. She works hard every day to turn that dream into a reality. Firsthand accounts from Cynthia and from those who know her best combine to tell the inspiring story of a curious, sports-loving girl who went on to become a worldclass roboticist. Robo World is also a Captivating story of high-tech invention where the stuff of science fiction becomes real in today's labs. This title aligns to Common Core standards: Interest Level Grades 6 - 8; Reading Level Grade level Equivalent: 7.1: Lexile Measure: 1080L; DRA: Not Available; Guided Reading: Z
Keywords: Explore Science

Space Rocks: The Story of Planetary Geologist Adriana Ocampo - Hopping, Lorraine Jean (The National Academies Press, 2006)
Adriana Ocampo grew up in Buenos Aires, Argentina, dreaming about exploring planets. She never doubted that all her dreams would come true someday. How did Adriana land a job with NASA, the U.S. space agency, while still in her teens? How did a robot parked on Mars make her fall in love with rocks and instantly decide to become a planetary geologist? Adriana's imagination and can-do attitude have led her to a life of science adventures. Adriana helped find the missing Crater of Doom, a hole blasted out of Earth by a killer space rock 65 million years ago, when the dinosaurs died out. Now she's searching the world for the stuff that came from that crater. Between rock digs she explores other planets through the electronic eyes of NASA's robotic spacecraft. How did an imaginative young girl with a dream of space exploration become a planetary geologist? Author Lorraine Jean Hopping makes the woman and her science come to life on every page, delighting readers of all ages. This title aligns to Common Core standards: Interest Level Grades 6 - 8; Reading Level Grade level Equivalent: 7.1: Lexile Measure: 1080L; DRA: Not Available; Guided Reading: Z
Keywords: Explore Science

Bone Detective: The Story of Forensic Anthropologist Diane France - Hopping, Lorraine Jean (The National Academies Press, 2006)
Diane France loves bones. Why? Because they talk to her. Every skeleton she meets whispers secrets about the life—and death—of its owner. Diane France can hear those secrets because she's a forensic anthropologist, a bone detective. She has the science skills and know-how to examine bones for clues to a mystery: Who was this person and how did he or she die? Bones tell Diane about the life and times of famous people in history, from a Russian royal family to American outlaws and war heroes. They speak to her about murders, mass disasters, and fatal accidents. One day she's collecting skeletal evidence at a crime scene. A phone call later she's jetting to the site of a plane crash or other unexpected tragedy to identify victims. Young readers will be captivated by the thrilling real-life story of this small-town girl full of curiosity and mischief who became a world-famous bone detective. This title aligns to Common Core standards: Interest Level Grades 6 - 8; Reading Level Grade level Equivalent: 7.1: Lexile Measure: 1080L; DRA: Not Available; Guided Reading: Z
Keywords: Explore Science

The Man Who Stopped Time: The Illuminating Story of Eadweard Muybridge — Pioneer Photographer, Father of the Motion Picture, Murderer - Clegg, Brian (The National Academies Press, 2007)
The photographs of Eadweard Muybridge are immediately familiar to us. Less familiar is the dramatic personal story of this seminal and wonderfully eccentric Victorian pioneer, now brought to life for the first time in this engaging and thoroughly entertaining biography.
Keywords: Explore Science; Biography and Autobiography

The Last Sorcerers: The Path from Alchemy to the Periodic Table - Morris, Richard (The National Academies Press, 2003)
They started with four: earth, air, fire, and water. From these basics, they sought to understand the essential ingredients of the world. Those who could see further, those who understood that the four were just the beginning, were the last sorcerers – and the world’s first chemists.
Keywords: Explore Science; Biography and Autobiography

Future of American Science - National Research Council (The National Academies Press, 1979)
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 80 - National Academy of Sciences (The National Academies Press, 2001)
Biographic Memoirs: Volume 80 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 88 - National Academy of Sciences (The National Academies Press, 2006)
Biographic Memoirs Volume 88 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 76 - National Academy of Sciences (The National Academies Press, 1999)
Biographic Memoirs: Volume 76 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 82 - National Academy of Sciences (The National Academies Press, 2003)
Biographic Memoirs Volume 82 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 11 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2007)
This is the 11th Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 83 - National Academy of Sciences (The National Academies Press, 2003)
Biographic Memoirs Volume 83 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 68 - National Academy of Sciences (The National Academies Press, 1995)
Biographic Memoirs: Volume 68 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 79 - National Academy of Sciences (The National Academies Press, 2001)
Biographic Memoirs: Volume 79 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 9 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2001)
This is the 9th Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 59 - National Academy of Sciences (The National Academies Press, 1990)
Biographic Memoirs: Volume 59 contains short biographies of deceased members of the National Academy of Sciences.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 70 - National Academy of Sciences (The National Academies Press, 1996)
Biographic Memoirs: Volume 70 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 72 - National Academy of Sciences (The National Academies Press, 1997)
Biographic Memoirs: Volume 72 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography